The economy of Indonesia; selected readings - Glassburner, Bruce (Ithaca: Cornell University Press, 1971)
This collection of articles and papers brings together a number of significant, widely scattered short works. The articles were chosen with a view toward giving the historical record of economic performance and economic policy since Indonesia achieved independence in late 1949.
Includes bibliographical references.
rpm 13/06/2017
Loans
Keywords: Economic history; Economic policy; Indonesia $1 (BEconomic conditions.s; Indonesia $1 (BEconomic conditions $1 (B1945-s; Indonesia $1 (BEconomic conditions $1 (B1945-1966.s; Indonesia $1 (BEconomic conditions $1 (B1945- $1 (BAddresses, essays, lecturess; Indonesia $1 (BEconomic conditions $1 (BReadingss; Indonesia $1 (BEconomic policy.s; Indonesia $1 (BEconomic policy $1 (BAddresses, essays, lecturess; Indonesia $1 (BEconomic conditions $1 (B1966-1997.s; Indonesia